2017
DOI: 10.1186/s12954-017-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal and case-control study of dropout among drug users in methadone maintenance treatment in Haiphong, Vietnam

Abstract: BackgroundVietnam began providing methadone maintenance therapy (MMT) in 2008; as of June 2016, 44,479 persons who inject drugs (PWID) were in treatment in 57 provinces. However, 10–23% of patients were estimated to have dropped out of treatment during the first 2 years. We evaluated dropout and factors associated with quitting treatment.MethodsWe followed clients ≥ 18 years old enrolled in five MMT clinics in Haiphong for 3 years. Persons who missed a consecutive month of methadone treatment were considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…This concern explained the attempt by some participants to get the lowest dose possible by asking to be tapered off even when they had no immediate plan to quit treatment. While this practice has not been commonly reported, it remains worrisome, as an inadequately low dose is a risk factor for abandoning treatment in many programmes (Khue et al, 2017;Proctor et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concern explained the attempt by some participants to get the lowest dose possible by asking to be tapered off even when they had no immediate plan to quit treatment. While this practice has not been commonly reported, it remains worrisome, as an inadequately low dose is a risk factor for abandoning treatment in many programmes (Khue et al, 2017;Proctor et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Of the government's 2015 target of 80,000 patients (estimated at 40% of all opioid users), only 52,054 were following treatment in July 2017, a 5,600 increase from the previous year (Social Republic of Vietnam, 2014;Vietnam Administration of AIDS Centre, 2016, 2017a. Meanwhile, overdose deaths, police arrests for drug-related crimes, side effects, and lack of motivation to continue with treatment raised dropout rates as high as 33.3% at 36 months (Khue et al, 2017). While this figure is similar in other countries (Huissoud, Rousson, & Dubois-Arber, 2012;Zhang et al, 2013), it is important to understand why participants decide to drop out in the specific context of Vietnam, where MMT has received strong support from the government.…”
Section: Context: the Introduction Of Mmt In Vietnammentioning
confidence: 99%
“…Stigma and lack of access to sufficient MT have limited patient recovery. Studies evaluating MT patient dropouts and utilization in injection drug-using populations in several countries have shown that high levels of social stigma and insufficient doses of methadone correlate with incomplete treatment adherence, early termination, or low levels of program utilization Tran et al, 2018;Khue et al, 2017). This is especially true outside major urban areas (Van Nguyen et al, 2017;Pham et al, 2017).…”
Section: Demand Reductionmentioning
confidence: 99%
“…This indicates that user fees may be a cause of dropout, as has been found in a previous casecontrol study set in Haiphong. 32 However, considering that about 5.6% of patients in provinces with user fees dropped out of MMT, user fees possibly were the primary cause of less than 1% of all patients at baseline to drop out. Patients retained in care stated that user fees were a contributing factor to stopping MMT in fewer than 15% of people they knew who stopped MMT, again suggesting that user fees were a contributing factor to stopping MMT in less than 1% of baseline patients.…”
Section: Discussionmentioning
confidence: 99%